Associations between climate change-related factors and sexual health: A scoping review - Logie, Carmen H.; Toccalino, Danielle; MacKenzie, Frannie; Hasham, Aryssa; Narasimhan, Manjulaa; Donkers, Holly; Lorimer, Nicole; Malama, Kalonde (Global Public Health, 2024)
There is growing attention to the ways in which climate change may affect sexual health, yet key knowledge gaps remain across global contexts and climate issues. In response, we conducted a scoping review to examine the literature on associations between climate change and sexual health. We searched five databases (May 2021, September 2022). We reviewed 3,183 non-duplicate records for inclusion; n = 83 articles met inclusion criteria. Of these articles, n = 30 focused on HIV and other STIs, n = 52 focused on sexual and gender-based violence (GBV), and n = 1 focused on comprehensive sexuality education. Thematic analysis revealed that hurricanes, drought, temperature variation, flooding, and storms may influence HIV outcomes among people with HIV by constraining access to antiretroviral treatment and worsening mental health. Climate change was associated with HIV/STI testing barriers and worsened economic conditions that elevated HIV exposure (e.g. transactional sex). Findings varied regarding associations between GBV with storms and drought, yet most studies examining flooding, extreme temperatures, and bushfires reported positive associations with GBV. Future climate change research can examine understudied sexual health domains and a range of climate-related issues (e.g. heat waves, deforestation) for their relevance to sexual health. Climate-resilient sexual health approaches can integrate extreme weather events into programming.